El autocuidado y su papel en la promoción de la salud (1999)
ABSTRACT: This paper reviews historically the Western practices and believes concerning care, taking into account the importance of self-care in the promotion of life and welfare of human beings. This may explain, in part, nowadays care practices as well as understand meaning of health promotion and face the responsibility of it. Then, in the framework of new approaches about health and health promotion, it proposes a new of assuming self-care from a human point of view as a basic strategy to promote human's’ life and welfare, according to their cultural characteristics in ethnics, social class, and vital cycle.